Specificity of Nuclear Size Scaling in Frog Erythrocytes - Niide, Tetsufumi; Asari, Saki; Kawabata, Kosuke; Hara, Yuki (Frontiers in Cell and Developmental Biology, 2022)
In eukaryotes, the cell has the ability to modulate the size of the nucleus depending on the surrounding environment, to enable nuclear functions such as DNA replication and transcription. From previous analyses of nuclear size scaling in various cell types and species, it has been found that eukaryotic cells have a conserved scaling rule, in which the nuclear size correlates with both cellular size and genomic content. However, there are few studies that have focused on a certain cell type and systematically analyzed the size scaling properties in individual species (intra-species) and among species (inter-species), and thus, the difference in the scaling rules among cell types and species is not well understood. In the present study, we analyzed the size scaling relationship among three parameters, nuclear size, cell size, and genomic content, in our measured datasets of terminally differentiated erythrocytes of five Anura frogs and collected datasets of different species classes from published papers. In the datasets of isolated erythrocytes from individual frogs, we found a very weak correlation between the measured nuclear and cell cross-sectional areas. Within the erythrocytes of individual species, the correlation of the nuclear area with the cell area showed a very low hypoallometric relationship, in which the relative nuclear size decreased when the cell size increased. These scaling trends in intra-species erythrocytes are not comparable to the known general correlation in other cell types. When comparing parameters across species, the nuclear areas correlated remarkably with both cell areas and genomic contents among the five frogs and the collected datasets in each species class. However, the contribution of genomic content to nuclear size determination was substantially smaller than that of the cell area in all species classes. In particular, the estimated degree of the contribution of genomic content was greater in the amphibian class than in other classes. Together with our imaging analysis of structural components in nuclear membranes, we hypothesized that the observed specific features in nuclear size scaling are achieved by the weak interaction of the chromatin with the nuclear membrane seen in frog erythrocytes.